2015
DOI: 10.1097/hjh.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

The effect of losartan on differential reflex control of sympathetic nerve activity in chronic kidney disease

Abstract: Inhibition of the AT1R selectively improved baroreflex control of sSNA and peripheral chemoreflex control of all three sympathetic nerve outflows in the LPK rat, suggesting these anomalies in reflex function are driven in part by angiotensin II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…We also sought to identify if altered sympathetic activity in the conscious LPK is associated with deficits in regulatory pathways known to impact autonomic neuroregulation of the cardiovascular system including the chemoreceptor reflex and behavioral stress. Tonic activation of excitatory chemoreceptor afferents has been proposed as a driver of elevated SNA in CKD patients (Hering et al, 2007 ; Despas et al, 2009 ) and we have recently shown under anesthetized conditions that the LPK animals have impaired peripheral and central chemoreflex responses (Yao et al, 2015 ). Accordingly, our second aim was to assess RSNA and blood pressure responses to central (hypercapnia) and peripheral (hypoxia) chemoreceptor stimulation in the conscious LPK.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…We also sought to identify if altered sympathetic activity in the conscious LPK is associated with deficits in regulatory pathways known to impact autonomic neuroregulation of the cardiovascular system including the chemoreceptor reflex and behavioral stress. Tonic activation of excitatory chemoreceptor afferents has been proposed as a driver of elevated SNA in CKD patients (Hering et al, 2007 ; Despas et al, 2009 ) and we have recently shown under anesthetized conditions that the LPK animals have impaired peripheral and central chemoreflex responses (Yao et al, 2015 ). Accordingly, our second aim was to assess RSNA and blood pressure responses to central (hypercapnia) and peripheral (hypoxia) chemoreceptor stimulation in the conscious LPK.…”
Section: Introductionmentioning
confidence: 84%
“…Indirectly, hypotensive responses to ganglionic blockade (Phillips et al, 2007 ; Ameer et al, 2014 ), bradycardic responses to β 1 -adrenoceptor blockade (Harrison et al, 2010 ) and low-frequency power of systolic blood pressure variability (Harrison et al, 2010 ; Hildreth et al, 2013b ) are all increased in the LPK. Directly, we have recently shown that RSNA in anesthetized animals display elevated absolute baseline tonic levels (Salman et al, 2014 , 2015 ; Yao et al, 2015 ). Given the potential effect of anesthesia on SNA, which may be influenced to a greater degree in the disease state (Hildreth et al, 2013a ), a key objective of the present study was to record RSNA in conscious unrestrained animals using telemetry, examining the hypothesis that a sustained elevation in RSNA is a key pathological feature of CKD.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The left renal sympathetic nerve was prepared and recorded using bipolar silver hook electrodes as described previously (Yao et al 2015). The activity was amplified (10,000×) and filtered (100-1000 Hz).…”
Section: Role Of Glycine In the Rvlm On Arterial Baroreflex Responsesmentioning
confidence: 99%
“…Hypertension, which is present in~80-85 % of CKD patients [4,5], is a powerful indicator of CVD and an independent risk factor for disease progression both in adult and in pediatric patients with CKD [5,7]. Several mechanisms have been implicated in the pathogenesis of hypertension and CVD in CKD, including sodium retention and fluid overload due to defects in the pressure natriuresis relationship, activation of the renin-angiotensinaldosterone system (RAAS) [8,9,10•], sympathetic nervous system (SNS) hyperactivity [9, 11, 12••, 13••], autonomic dysfunction [13••, 14, 15], endogenous and environmental stress [5,16], impaired endothelial function, vascular remodeling, and arterial calcification [17,18], thus highlighting a complex interplay of neural, hormonal, and vascular mechanisms linking kidney disease to high blood pressure (BP) and the associated cardiovascular problems that consequently arise.…”
Section: Introductionmentioning
confidence: 99%